PERAN PERENCANAAN KEUANGAN PRIBADI DALAM MEWUJUDKAN STABILITAS KEUANGAN MAHASISWA DI TENGAH TREN GAYA HIDUP DIGITAL - Dewi Aisyah Eldiani Boru Tobing; Kristina Wanti Aritonang; Revalia Khumairani; Ines Imelda ZR (CV. Denasya Smart Publisher, 2026)
The development of a digital lifestyle influences students’ financial management behavior. This study aims to understand how students plan and manage their personal finances in the digital era. This research employs a descriptive qualitative approach, with data collected through semi-structured interviews involving five active students from the University of Bengkulu selected using purposive sampling. The findings indicate that students generally have an initial awareness of financial planning, such as budgeting their allowances and saving money; however, these practices are not consistently implemented and lack structured financial records. Furthermore, the ease of digital financial services enhances transaction efficiency while simultaneously increasing consumptive behavior, particularly due to promotions and paylater features. The main challenges include limited income and low control over spending. This study concludes that students’ financial stability is determined by the balance between financial literacy, financial planning, and consumption control.